An international collaborative investigation of beginning seventh grade students' understandings of scientific inquiry: Establishing a baseline. Issue 4 (4th January 2019) - Lederman, Judith; Lederman, Norman; Bartels, Selina; Jimenez, Juan; Akubo, Mark; Aly, Shereen; Bao, Chengcheng; Blanquet, Estelle; Blonder, Ron; Bologna Soares de Andrade, Mariana; Buntting, Catherine; Cakir, Mustafa; et al.
Abstract : Although understandings of scientific inquiry (as opposed to conducting inquiry) are included in science education reform documents around the world, little is known about what students have learned about inquiry during their elementary school years. This is partially due to the lack of any assessment instrument to measure understandings about scientific inquiry. However, a valid and reliable assessment has recently been developed and published, Views About Scientific Inquiry (VASI; Lederman et al. [2014], Journal of Research in Science Teaching, 51, 65–83). The purpose of this large‐scale international project was to collect the first baseline data on what beginning middle school students have learned about scientific inquiry during their elementary school years. Eighteen countries/regions spanning six continents including 2, 634 students participated in the study. The participating countries/regions were: Australia, Brazil, Chile, Egypt, England, Finland, France, Germany, Israel, Mainland China, New Zealand, Nigeria, South Africa, Spain, Sweden, Taiwan, Turkey, and the United States. In many countries, science is not formally taught until middle school, which is the rationale for choosing seventh grade students for this investigation. This baseline data will simultaneously provide information on what, if anything, students learn about inquiry in elementary school, as well as their beginning knowledge as they enter secondary school. It is important to note that collecting data from all of the approximately 200 countries globally was not humanly possible, and it was also not possible to collect data from every region of each country. The results overwhelmingly show that students around the world at the beginning of grade seven have very little understandings about scientific inquiry. Some countries do show reasonable understandings in certain aspects but the overall picture of understandings of scientific inquiry is not what is hoped for after completing 6 years of elementary education in any country.